Specificity of the diagnostic materials for laryngopharyngeal reflux. - Logan, Jeanneane (My University, 2011)
Rationale: Laryngopharygeal reflux (LPR) is a controversial area of diagnosis and consequently management. Many patients suffering from voice and swallowing disorders may be suffering from LPR but decreased specificity of diagnosis makes management ineffective and impacts on quality of life as well as leading to overdiagnosis of LPR. Aims: (1) To establish the relationship between the Reflux Symptom Index (RSI) and the Reflux Finding Score (RFS) in participants who have attended the Wits University Donald Gordon Voice and Swallowing clinic. (2) To establish if there is a correlation between the total RFS and RSI scores. (3) To ascertain which test items of the RSI and the RFS are elevated in the participants. (4) To describe trends in RFS and RSI sub scores and (5) to determine if extraneous factors such as age, gender, professional voice use and smoking impact on the subscores of the RFS and RSI and to describe the trends based on these variables Method: A quantitative retrospective chart review of 105 patients who attended the Voice and Swallowing clinic was conducted. Each participant completed a self-rating scale for reflux severity (the RSI) as well as undergoing stroboscopic examination. Stroboscopic results were rated by a multidisciplinary team (2 otolaryngologists, a speech therapist and a voice coach) to ascertain the patient’s Reflux Finding Score (RFS). Inferential and descriptive statistics were employed to achieve the aims. Results: A weak negative significant correlation on totals of the RFS and RSI (r=0,20; p= 0,0395) was established. There were a number of intra-item correlations on the RSI and the RFS. Descriptive statistics revealed that hoarseness, excess mucus and throat clearing were the most frequently rated symptoms on the RSI and erythemia, posterior commisure hyperatrophy and diffuse laryngeal oedema most frequently rated signs on the RFS. Gender was the only variable found to have a significant effect on the total RFS and RSI ratings. Conclusion: There is specificity in the RSI and RFS as diagnostic materials for LPR. However, there may be an incidence of over diagnosis. Factors such as age, smoking, professional voice use and gender must be considered in diagnosis.
Keywords: Voice disorders; Laryngopharyngeal reflux; Reflux finding score; Reflux severity index